Investigating Erin Gruwell's Ambition in Richard Lagravenese's Freedom Writers Movie (2007) from Murray's Personology - Prima Indah Suryo Kinanti; Syahara Dina Amalia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study aims to investigate the ambition of Erin Gruwell, the main figure in the film Freedom Writers (2007). Personology theory by Henry Murray was used to investigate the ambition values contained in Erin Gruwell's character. The researcher used qualitative descriptive research, from which the primary data sources were selected from the script of the Freedom Writers (2007) movie, and the secondary data sources were selected from other sources related to previous research, websites, ebooks, and other articles. The results of this study can be classified into three. Firstly, Murray's theory about personology, showed that Erin’s id came from Erin when she had a motivation for being a teacher. Erin’s ego brought her to do something to realize her ambition, and Erin’s superego continued to struggle for her goals. Secondly, the type of ambition needs depicted in the main character is psychogenic needs or secondary needs that contain achievement, recognition, and exhibition. Thirdly, ambition brought the main character in a positive direction and had an impact on herself as well as on her surroundings